Hidrox® and Chronic Cystitis: Biochemical Evaluation of Inflammation, Oxidative Stress, and Pain - Ramona D'Amico; Angela Trovato Salinaro; Marika Cordaro; Roberta Fusco; Daniela Impellizzeri; Livia Interdonato; Maria Scuto; Maria Laura Ontario; Roberto Crea; Rosalba Siracusa; Salvatore Cuzzocrea; Rosanna Di Paola; et al. (MDPI AG, 2021)
Interstitial cystitis/painful bladder syndrome (IC/PBS) is a chronic bladder condition characterized by frequent urination, inflammation, oxidative stress, and pain. The aim of the study was to evaluate the anti-inflammatory and antioxidant effects of an oral administration of Hidrox® (10 mg/kg) in the bladder and spinal cord in a rodent model of IC/BPS. The chronic animal model of cystitis was induced by repeated intraperitoneal injections of cyclophosphamide (CYP) for five consecutive days. Treatment with Hidrox® began on the third day of the CYP injection and continued until the 10th day. CYP administration caused macroscopic and histological bladder changes, inflammatory infiltrates, increased mast cell numbers, oxidative stress, decreased expression of the tight endothelial junction (e.g., zonula occludens-1 (ZO-1) and occludin), and bladder pain. Treatment with Hidrox® was able to improve CYP-induced inflammation and oxidative stress via the nuclear factor erythroid 2-related factor 2 (Nrf2)/heme oxygenase 1 (HO-1) pathway. It was also able to reduce bladder pain which was aggravated by the activation of neuroinflammation in the central nervous system. In particular, Hidrox® reduced the brain-derived neurotrophic factor (BDNF), as well as the activation of astrocytes and microglia, consequently reducing mechanical allodynia. These results indicate that nutritional consumption of Hidrox® can be considered as a new therapeutic approach for human cystitis, increasing the conceivable potential of a significant improvement in the quality of life associated with a lowering of symptom intensity in patients with IC/BPS.